Object Detection with a Webcam Using the Python Programming Language - Ali Basrah Pulungan; Zhafranul Nafis; Muhammad Anwar; Hastuti Hastuti; Hamdani Hamdani; Dwiprima Elvanny Myori Myori (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2021)
Technology developed rapidly along the times, various ways are done to make works easier. One of them is by utilizing artificial intelligence, likes the use of a webcam as a sensor in detecting an object through several stages of image processing. There was research on object recognition previously using three measurement parameters based on color, shape, and size of objects. It is used a webcam as the sensing sensor, and image processing is processed with python programming. In this article, writer described about image processing for the detection of objects used in the research. The results of this device have been tested and are able to detect objects properly based on predetermined color, shape and size. Object detection using a webcam can work properly according to what the author wants.